Satisfaction of neurosurgery outpatients of the Instituto Nacional de Ciencias Neurológicas, Lima - Peru, 2016 - Robles Hurtado, Isabel (2019)
Objective: To determine the satisfaction level of neurosurgery outpatients of the Instituto Nacional de Ciencias Neurológicas (INCN), Lima, from October to November 2016. Materials and methods: A quantitative, descriptive, prospective and cross-sectional study was conducted in 314 patients. The study used the SERVQUAL survey to calculate the mean differential score, as well as the ANCOVA analysis and the Spearman’s rank correlation coefficient. Results: Overall satisfaction accounted for 19.4 % (61) and overall dissatisfaction, 80.6 % (253), which included both mild and moderate dissatisfaction. Fifty-five point one percent (55.1 %) (173) of middle-aged adults expressed overall dissatisfaction. The mean differential score for all the dimensions reached 0.77 (reliability 0.91, responsiveness 0.85, safety 0.44, empathy 1.03 and tangible aspects 0.52). Middle-aged adults presented dissatisfaction in all dimensions: tangibility 36.6 % (115), reliability 13.3 % (42), responsiveness 46.8 % (147), safety 14.9 % (47) and empathy 55.1 % (173). A statistically significant low positive correlation was observed between patients’ education level and satisfaction with appointment scheduling (r = 0.185), patients’ education level and respect for privacy (r = 0.196), and type of patient and fast radiological examination service (r = 0.184). A statistically significant low negative correlation was observed between patients’ education level and satisfaction with regard to understanding the neurosurgeon’s explanations of the treatment (r = -0.212), adequacy of posters and signs for orientation (r = -0.233), availability of equipment and materials needed for healthcare (r = -0.175), and cleanliness and comfort of the waiting room (r = -0.175). Conclusions: Four (4) out of five (5) patients expressed dissatisfaction. A direct correlation was observed between patients’ education level and satisfaction with appointment scheduling and respect for privacy. Patients’ origin was associated with understanding the neurosurgeon’s explanations of the treatment.